2006
DOI: 10.1063/1.2165643
|View full text |Cite
|
Sign up to set email alerts
|

Universal Scaling of Resonances in Vector Correlation Photoionization Parameters

Abstract: In the present work it is shown that in atomic photoionization the Fanolike behaviour of vector correlation parameters in the region of an isolated autoionizing resonance possesses two universal values: the width and the energy shift with respect to the energy of the autoionizing state. This property is confirmed by fluorescence polarimetry studies, which provide, in the particular case of Xe 4d −1 5/2 6p (J = 1) photoexcitation, the experimental determination of the alignment and the orientation of the final … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…For a single resonance coupled to more than one asymptotic continuum, it was shown that the analysis could be transformed to that of the resonant state decaying to a single-channel plus a sum of non-interacting channels formed as linear combinations of the original channels. Later developments 39 41 provided expressions for the line shapes for decay to the original asymptotic channels, which when added together yield the same profiles as found in the original paper by Fano. Two-channel Fano-like parameterizations have recently been applied to predict the angular dependence of atomic photoionization time delays in the laboratory frame 14 .…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…For a single resonance coupled to more than one asymptotic continuum, it was shown that the analysis could be transformed to that of the resonant state decaying to a single-channel plus a sum of non-interacting channels formed as linear combinations of the original channels. Later developments 39 41 provided expressions for the line shapes for decay to the original asymptotic channels, which when added together yield the same profiles as found in the original paper by Fano. Two-channel Fano-like parameterizations have recently been applied to predict the angular dependence of atomic photoionization time delays in the laboratory frame 14 .…”
Section: Resultsmentioning
confidence: 67%
“…The remarkable photoionization dynamics featured in Fig. 2 in the region of the shape resonance can be interpreted based on a Fano line-shape analysis 38 as applied to multichannel problems 39 41 . The analysis models the contributions of resonant and non-resonant photoionization amplitudes that coherently add to yield the total PDA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation